A remote sensing and GIS-based analysis on the impact of dam construction towards the land use land cover pattern of Bakreswar Watershed, India - Bhandary, Arpita; Roy, Poushali (Acta Geographica Debrecina Landscape & Environment series, 2025)
The present study evaluates the impact of the dam construction on land use and land cover (LULC) pattern of the Bakreswar Watershed in the Birbhum District, West Bengal, India during 1990-2020. Landsat 5 TM and Landsat 8 OLI data were used to analyze the LULC pattern during the pre- and post-dam construction periods. Supervised image classification using the maximum likelihood algorithm was done to generate LULC and change detection maps in ArcGIS. LULC dynamic attitude and transfer matrix were prepared based on the LULC maps of four years. The results show that the dam construction significantly influenced the LULC pattern of the region. The highest rate of increase is seen in waterbody (86.37%) during 1990–2000 due to dam construction. Cultivated land also increased by 12.31% during this period. After the dam construction, the conversion rate from fallow land to cultivated land is higher in the downstream area rather than the upstream area. The area under barren land decreased by 53.28% in 1990–2000 and by 41.23% during 2009–2020 due to its conversion to built-up area. The built-up area rapidly increased during the past 20 years, by 34.57% and 45% during 1990–2000 and 2009-2020, respectively. Major change is seen along the Panagarh–Morgram Highway which connects two urban centers, Suri and Dubrajpur. Settlement concentration is also high around the Bakreswar Thermal Power Plant (BkTPP) and BkTPP Township. This study provides a useful approach to understanding the impacts of dam construction on cultivated area change and how transportation facility influences urban agglomeration.